The Hermite Hadamard Inequality on Hypercuboid - Alomari, Mohammad W (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
Given any a := (a1; a2,... ; an) and b := (b1; b2;... ; bn) in Rn. The n-fold convex function dened on [a; b], a; b 2 Rn with a < b is a convex function in each variable separately. In this work we prove an inequality of Hermite-Hadamard type for n-fold convex functions. Namely, we establish the inequality